Synthesis of Methyl Citronellate through Fischer Esterification Reaction between Methanol and Citronellic Acid from Oxidation Product of Citronellal - Wahyono, Joko; Budimarwanti, Cornelia (Universitas Negeri Yogyakarta, 2025)
The purpose of this research was to synthesis methyl citronellate through Fischer esterification reaction between methanol and citronellic acid from oxidation product of citronellal and characterize the methyl citronellate of esterification product by TLC method, IR spectroscopy, and GC-MS. This research was started by oxidizing citronellal to citronellic acid using silver oxide (Ag2O) oxidator obtained from reaction between silver nitrate (AgNO3) with sodium hydoxide (NaOH) and oxidation reaction at temperature of 55-60oC for 35 minutes. Then, the oxidation product of citronellal was reacted with methanol through Fischer esterification reaction using concentrated sulfuric acid (H2SO4) catalyst at 46oC for 2 hours. The products of citronellal oxidation and esterification were identified using TLC, IR spectrophotometer, and GC-MS. The result of this research showed that the Fischer esterification reaction between methanol with citronellic acid from oxidation product of citronellal was produce methyl citronellate in the form of brownish yellow liquid and smelled fragrant. The result of methyl citronellate from esterification product characterization by using TLC method, IR spectroscopy, and GC-MS showed that the methyl citronellate has a purity of 17 % and a yield of 13.76 %.